A Constitutive Model Research Based on Dislocation Mechanism of 5083 Aluminum Alloy. (27th November 2017) - Gao, N.; Zhu, Z.; Xiao, S.; Xie, Q.
Abstract : The study of the mechanical properties of polycrystalline alloy materials under dynamic impact, namely, the prediction of mechanical behavior after yield stress and the establishment of a constitutive model, has attracted much attention in the field of engineering. The stress-strain curves of 5083 aluminum alloy were obtained under strain rates varying from 0.0002 s -1 to 7130 s -1 through uniaxial compression experiments. The equipment used included a CRIMS RPL100 tester, Instron tester, and split Hopkinson test system. In addition, based on dislocation dynamics and the strengthening mechanism of metals, the plastic flow of the 5083 aluminum alloy was systematically analyzed under a wide range of strain rates. It was found that the abnormal yield behavior of the 5083 aluminum alloy under a wide range of strain rates increased, and the experimental phenomenon of hardening rate decreased with an increase in strain rate. This study also revealed that the abnormal yield behavior is caused by the different dislocation mechanisms of two-phase alloy elements under different strain rates. Based on the thermal activation theory and the experimental data, a constitutive model was developed. A comparison showed good agreement between the experimental and model curves. This indicates that this model has good plastic flow stress prediction ability for such types of materials.